The Twenty-First Century Commercial Space Imperative - Young, Anthony (SpringerBriefs in Space Development, 2015)
Young addresses the impressive expansion across existing and developing commercial space business markets, with multiple private companies competing in the payload launch services sector. The author pinpoints the new markets, technologies, and players in the industry, as well as highlighting the overall reasons why it is important for us to develop space. NASA now relies on commercial partners to supply cargo and crew spacecraft and services to and from the International Space Station. The sizes of satellites are diminishing and their capabilities expanding, while costs to orbit are decreasing. Suborbital space tourism holds the potential of new industries and jobs. Commercial space exploration of the Moon and the planets also holds promise. All this activity is a catalyst for anyone interested in joining the developing space industry, from students and researchers to engineers and entrepreneurs. As more and more satellites and rockets are launched and the business of space is expanding at a significant pace, it is increasingly important for scientists and engineers of many disciplines to understand how the business evolved and where it is continuing to develop. The growing field is fully explored in this concise overview to the players in this changing landscape.